2016
DOI: 10.1111/1750-3841.13352
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiling Using Uplc Q‐Tof/Ms and Antioxidant Activities of Fortunella Fruits

Abstract: The fruits of Fortunella Swingle are widely consumed as fresh fruits and traditional medicine in China. China is the origin center and has the largest cultivated area of the genus Fortunella. In this study, the chemical compositions of ethanol extracts of the major Fortunella cultivated types including Fortunella japonica Swingle, Fortunella margarita Swingle, Fortunella crassifolia Swingle 1 (Lanshang) and Fortunella crassifolia Swingle 2 (Liuyang) were determined using ultra performance liquid chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
(69 reference statements)
2
8
0
Order By: Relevance
“…These previous effects may be attributed to the presence of carotenoids which reported to have antioxidant activities as they are capable of scavenging ROS, inhibiting lipid peroxidation and inducing detoxifying enzymes (Yeh et al, 2009). Many studies revealed that F. margarita contains carotenoids including, β-Carotene, β-cryptoxanthin, lutein, violaxanthin and zeaxanthin (Schirra et al, 2007;Wang et al, 2007 Tan et al (2016) reported that the antioxidant capacity of F. margarita is very high and this is attributed to the high content of flavonoids since flavonoids were usually regarded as the basis of antioxidant capacity. It was reported that flavonoids strongly inhibit production of lipid peroxidation and enhance the endogenous antioxidant defense mechanism (Pavanato et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These previous effects may be attributed to the presence of carotenoids which reported to have antioxidant activities as they are capable of scavenging ROS, inhibiting lipid peroxidation and inducing detoxifying enzymes (Yeh et al, 2009). Many studies revealed that F. margarita contains carotenoids including, β-Carotene, β-cryptoxanthin, lutein, violaxanthin and zeaxanthin (Schirra et al, 2007;Wang et al, 2007 Tan et al (2016) reported that the antioxidant capacity of F. margarita is very high and this is attributed to the high content of flavonoids since flavonoids were usually regarded as the basis of antioxidant capacity. It was reported that flavonoids strongly inhibit production of lipid peroxidation and enhance the endogenous antioxidant defense mechanism (Pavanato et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional HPLC, UHPLC is proven to be an efficient chromatographic separation tool, which not only has higher analytical sensitivity and better peak shapes, but also gives a greater resolution within a shorter retention time . Besides, UHPLC can be coupled to Q‐TOF‐MS, which provides improved mass measurement accuracy and high sensitivity to make the detection easier than UV detection, especially for those non‐UV‐absorbing terpenes in traditional herbal medicine . Moreover, MS detection can provide more extensive structural information than UV, even in the absence of standard samples .…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant potential of volatile compounds is well established as phenolics and secondary metabolites with conjugated double bonds [ 34 ]. All citrus essential oils have radical-scavenging activity, the efficacy of which seems to depend on the content of such compounds as γ-terpinene, terpinolene, and citral, all of which exhibit notable activity [ 35 , 36 ]. According to the previous literature, carvacrol, which is found in the essential oils of thymol and origanum, has DPPH-scavenging capacity [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…All citrus essential oils have radical-scavenging activity, the efficacy of which seems to depend on the content of such compounds as γ-terpinene, terpinolene, and citral, all of which exhibit notable activity [ 35 , 36 ]. According to the previous literature, carvacrol, which is found in the essential oils of thymol and origanum, has DPPH-scavenging capacity [ 35 ]. Moreover, in essential oils of citrus fruits, citral has been found to have greater oxidation stability than limonene and linalool [ 37 ].…”
Section: Resultsmentioning
confidence: 99%